Detection of low Temperature heat release (LTHR) in the standard Cooperative Fuel Research (CFR) engine in both SI and HCCI combustion modes. (15th November 2019) - Waqas, Muhammad Umer; Hoth, Alexander; Kolodziej, Christopher P.; Rockstroh, Toby; Gonzalez, Jorge Pulpeiro; Johansson, Bengt
Abstract: To this date, extensive research has been conducted to understand the low-temperature auto-ignition chemistry of gasoline. The detection of low-temperature chemical reactions under Spark Ignition (SI) combustion cannot be detected, as they are hidden by the flame propagation. Alternatively, Homogeneous Charge Compression Ignition (HCCI) combustion has a two-stage combustion involving low and high-temperature heat release (LTHR and HTHR respectively). Both Knocking SI and HCCI combustion involve auto-ignition and are governed by fuel characteristics and the pressure-temperature (P-T) history. Therefore, HCCI combustion might provide an alternative to understand the knocking behavior and LTHR in modern SI engines. A standard Cooperative Fuel Research (CFR) engine was operated at lean HCCI conditions (lambda 3), as well as SI conditions at stoichiometry. For SI combustion, the CFR engine was operated with RON-like conditions, but at late spark timing to induce LTHR prior to flame propagation. Three RON 90 binary fuel blends were investigated, being composed of n -heptane with isooctane, toluene, or ethanol. This work demonstrated that the CFR engine under stoichiometric SI with late spark timing and HCCI combustion mode can help to detect LTHR which is not possible in the standard RON test. The intake pressure and temperature sweeps showed similar effects on LTHR for both combustion modes. The linking of auto-ignition behavior of SI and HCCI was dependent primarily on intake valve closing (IVC) conditions. The high exhaust temperature in SI lead to high IVC temperatures. In order to match the IVC temperatures and to overlap the P-T trajectories, the intake temperature for HCCI was increased.